Successful Treatment of Nivolumab-Resistant Multiple In-Transit Melanomas with Ipilimumab and Topical Imiquimod - Taku Fujimura; Yumi Kambayashi; Yota Sato; Kayo Tanita; Sadanori Furudate; Akira Tsukada; Hisayuki Tono; Akira Hashimoto; Setsuya Aiba (Case Reports in Oncology, 2018)
Simultaneous or sequential, planned administration of ipilimumab could significantly enhance the antitumor effects of nivolumab in advanced melanoma patients. On the other hand, the efficacy of ipilimumab for nivolumab-resistant advanced melanoma is extremely poor. Therefore, additional supportive therapy for anti-PD-1 antibody therapy-resistant advanced melanoma has been widely investigated. In this report, we describe a case of multiple in-transit melanomas developing in a nivolumab-resistant patient successfully treated with ipilimumab in combination with imiquimod. Our present case suggested a possible therapy for nivolumab-resistant multiple in-transit melanomas using ipilimumab in combination with topical imiquimod.